Comparison of CT Scan, X-Ray and Ultrasound in Sensitivity and Specificity for Identifying Kidney Stones in Clinical Settings? : A Comprehensive Systematic Review - Dovie Yullia Putri; Imam Baharsyah Azri (International Medical Journal Corp. Ltd, 2025)
Introduction: Kidney stones are a prevalent urological condition requiring accurate imaging for diagnosis and management. This study compares the sensitivity and specificity of three primary imaging modalities: computed tomography (CT), ultrasound, and X-ray. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, Semanthic Scholar, and Google Scholar., focusing on studies that evaluated the diagnostic performance of CT, ultrasound, and X-ray in detecting kidney stones. Sensitivity and specificity data were extracted and analyzed. Results: Non-contrast CT emerged as the gold standard, demonstrating sensitivity rates between 86% and 98% and specificity approaching 100%. Ultrasound, while radiation-free, showed variable sensitivity (72%-85%) influenced by operator skill. X-ray exhibited moderate sensitivity ( 78%) but was limited to detecting radiopaque stones. Combined imaging strategies, such as ultrasound followed by low-dose CT, improved diagnostic accuracy while minimizing radiation exposure. Discussion: The findings underscore the importance of selecting appropriate imaging modalities based on patient characteristics and clinical context. While CT offers superior diagnostic performance, ultrasound remains a valuable first-line tool, particularly in vulnerable populations. The integration of emerging technologies and combined imaging approaches may further enhance diagnostic capabilities. Conclusion: This analysis highlights the need for evidence-based imaging strategies in managing kidney stones, emphasizing the balance between diagnostic accuracy and patient safety. Future research should focus on optimizing imaging protocols and validating new technologies.